Tinjauan Literatur Perkembangan Teori Evolusi Manusia Dalam Sudut Pandang Mahasiswa Biologi - Pratama, Mega Septyana Putri (Maliki Interdisciplinary Journal, 2024)
Facts-Facts of human thought is discussed in many deskripsi and theories that inspire the following generation. When the theory can be tested experimentally, it can be regarded as an established theory. Likewise, the ahli and the knowledge that are mentioned in the historical narratives. From the beginning of the evolution to the present, there are many different perspectives. Despite this, there is a bukti that protects each argumen. The evolution of life will never stop and will encounter many challenges. They might achieve success or remain in the debate. All of us are descended from a single ancestor or are written down as a testament to the fact that God created us. Every detail is based on how you see and how much knowledge you have. However, it must be understood that if we want to understand that a particular statement is true, we must continue to remain steadfast in our pursuit of knowledge.